2020
DOI: 10.1080/1461670x.2020.1808516
|View full text |Cite
|
Sign up to set email alerts
|

“The Media Covers Up a Lot of Things”: Watchdog Ideals Meet Folk Theories of Journalism

Abstract: The idealized view of the press as an institution that operates independently from private and political interests and tries to hold power to account is central to many journalists' selfconception and extensive academic scholarship on news. Yet surveys find significant numbers of citizens reject such views about the role of news in society. This article draws on in-depth interviews with a strategic sample of 83 news avoiders in Spain and the UK to investigate "folk theories" about the relationship between news… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…Participants in the Mumsnet discussions also demonstrated levels of distrust in both the mainstream news media and the UK government in relation to the pandemic, confirming the findings of previous studies (Kyriakidou et al 2020;Nielsen et al 2020;Palmer et al 2020). There was a constant stream of criticism of the media in the threads analysedfor not adequately covering the pandemic before COVID-19 arrived in the UK; for not covering stories deemed important by Mumsnetters, such as the spread of the virus into care homes; for misleading coverage of particular stories; and for attempts to move the news agenda on, for example by focussing on the issue of when to lift the lockdown.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Participants in the Mumsnet discussions also demonstrated levels of distrust in both the mainstream news media and the UK government in relation to the pandemic, confirming the findings of previous studies (Kyriakidou et al 2020;Nielsen et al 2020;Palmer et al 2020). There was a constant stream of criticism of the media in the threads analysedfor not adequately covering the pandemic before COVID-19 arrived in the UK; for not covering stories deemed important by Mumsnetters, such as the spread of the virus into care homes; for misleading coverage of particular stories; and for attempts to move the news agenda on, for example by focussing on the issue of when to lift the lockdown.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, a third of news avoiders in the UK, of both sexes, did not trust the news. Palmer et al (2020) found that news avoiders saw the news media at best as irrelevant and, at worst, actively complicit with the political and economic establishment. A Reuters Institute study about the attitudes of people in the UK towards the media and government found that trust in government information declined from May 2020 due to perceived mismanagement and incompetence (Nielsen et al 2020).…”
Section: Contextmentioning
confidence: 99%
“…Terrance (30) believed NOS was most objective "because it is the state, by the state". While a close (perceived) relationship between government and news media is typically seen by audiences as less trustworthy (Palmer, Toff, and Nielsen 2020), for Terrance this "direct line" made him trust NOS more.…”
Section: Phase 4: Back To Normalmentioning
confidence: 99%
“…Autonomy from powerholders and not abiding to internal influences, such as the board of directors or the marketing department, and external influences, such as politicians or commercial companies, is of utmost importance to bring reliable information and to be able to scrutinize powerholders in a credible way. This idealized view of the press as an institution that operates independently from private and political interests and tries to hold power to account is central to many journalists' self-conception (Palmer et al 2020). Due to journalism's central role in society, it feels obliged to adhere to these high standards (Fawzi and Mothes 2020).…”
Section: Journalistic Professional Normsmentioning
confidence: 99%